MicroRNA‐143/Musashi‐2/KRAS cascade contributes positively to carcinogenesis in human bladder cancer. Issue 7 (27th May 2019) - Tsujino, Takuya; Sugito, Nobuhiko; Taniguchi, Kohei; Honda, Ryo; Komura, Kazumasa; Yoshikawa, Yuki; Takai, Tomoaki; Minami, Koichiro; Kuranaga, Yuki; Shinohara, Haruka; Tokumaru, Yoshihisa; Heishima, Kazuki; et al.
Abstract: It has been well established that microRNA (miR)‐143 is downregulated in human bladder cancer (BC). Recent precision medicine has shown that mutations in BC are frequently observed in FGFR3, RAS and PIK3CA genes, all of which correlate with RAS signaling networks. We have previously shown that miR‐143 suppresses cell growth by inhibiting RAS signaling networks in several cancers including BC. In the present study, we showed that synthetic miR‐143 negatively regulated the RNA‐binding protein Musashi‐2 (MSI2) in BC cell lines. MSI2 is an RNA‐binding protein that regulates the stability of certain mRNAs and their translation by binding to the target sequences of the mRNAs. Of note, the present study clarified that MSI2 positively regulated KRAS expression through directly binding to the target sequence of KRAS mRNA and promoting its translation, thus contributing to the maintenance of KRAS expression. Thus, miR‐143 silenced KRAS and MSI2, which further downregulated KRAS expression through perturbation of the MSI2/KRAS cascade. Abstract : MiR‐143 directly impacts KRAS and RNA‐binding protein MSI2. MSI2 enhances translation of KRAS through directly binding to mRNA of KRAS. KRAS controls the maintenance of KRAS signaling networks through the novel MSI2/KRAS cascade.